2007
DOI: 10.1042/cs20060103
|View full text |Cite
|
Sign up to set email alerts
|

Growth-hormone-releasing peptide 6 (GHRP6) prevents oxidant cytotoxicity and reduces myocardial necrosis in a model of acute myocardial infarction

Abstract: Therapies aimed at enhancing cardiomyocyte survival following myocardial injury are urgently required. As GHRP6 [GH (growth hormone)-releasing peptide 6] has been shown to stimulate GH secretion and has beneficial cardiovascular effects, the aim of the present study was to determine whether GHRP6 administration reduces myocardial infarct size following acute coronary occlusion in vivo. Female Cuban Creole pigs were anaesthetized, monitored and instrumented to ensure a complete sudden left circumflex artery occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Berlanga et al recently showed that GHRP-6 treatment attenuated the decrease in total SOD activity in a model of acute myocardial infarction. 30 On the other hand, in the present study GSHPx activity did not differ among all 4 groups at 12 weeks of age. Although our findings suggest that antioxidant capacity might be relatively preserved in untreated TO-2 hamsters at 12 weeks of age, further enhancement of total SOD activity might in part contribute to the antioxidative effects of GHRP-2 in TO-2 hamsters.…”
Section: Effects Of Ghrp-2 On Myocardial Oxidative Stress and Antioximentioning
confidence: 44%
“…Berlanga et al recently showed that GHRP-6 treatment attenuated the decrease in total SOD activity in a model of acute myocardial infarction. 30 On the other hand, in the present study GSHPx activity did not differ among all 4 groups at 12 weeks of age. Although our findings suggest that antioxidant capacity might be relatively preserved in untreated TO-2 hamsters at 12 weeks of age, further enhancement of total SOD activity might in part contribute to the antioxidative effects of GHRP-2 in TO-2 hamsters.…”
Section: Effects Of Ghrp-2 On Myocardial Oxidative Stress and Antioximentioning
confidence: 44%
“…Both are distinguished by their ability to turn multiple cell lineages into more tolerant before a broad spectrum of lethal insults (Berlanga et al 1998(Berlanga et al , 2002(Berlanga et al , 2007Caballero et al 2001;Cibrian et al 2006). EGF and GHRP-6 exhibit different biological properties which aim to hit the same pathophysiological targets, favoring at the end, neuronal and glial cells survival.…”
Section: Discussionmentioning
confidence: 98%
“…Previous administration of GHSs such as hexarelin or GHRP-6 leads, 2 h later, to a near complete blockade of GHRH-mediated GH secretion, a finding called heterologous desensitization. [22] Growth hormone secretagogues (GHSs) are synthetic peptidyl and nonpeptidyl compounds that are believed to stimulate the release of GH by a direct effect on the pituitary somatotroph and by stimulation of growth hormone-releasing hormone (GHRH) release and/or via functional antagonism of somatostatin (SRIH) tone. [24] They also binds and activate hypothalamic GHS-R. Maier's study shows that cholinergic blockade with ATR suppresses ghrelin plasma concentrations and modulation of the cholinergic system with ATR, but not PD, influences the ability of different ghrelin dosages to induce GH release.…”
Section: Discussionmentioning
confidence: 99%